Knowledge and attitudes among Lebanese pregnant women and women seeking fertility treatment during the COVID-19 outbreak: a cross-sectional survey - Hani Tamim; Lina El Taha; Christine Beyrouthy; Ghina Ghazeeri (BMJ Open)
Objectives COVID-19 has been recognised as a global health emergency necessitating collaborative efforts to halt further disease spread. The success of public health interventions and vaccination campaigns is contingent on the knowledge and awareness level of the public. We aim to assess COVID-19 knowledge and attitudes among Lebanese pregnant women and women seeking fertility treatment.Design Cross-sectional study using telehealth administered survey.Setting University-affiliated tertiary care centre.Participants The data of 402-Lebanese women pregnant or seeking fertility treatment aged 20–45 years were analysed.Outcome measures Extent of COVID-19 general knowledge, pregnancy-specific knowledge and attitudes toward COVID-19 practices.Results All participants reported being knowledgeable about COVID-19, 70% of which rated their knowledge as 7 or more on a numerical scale of 0–10. The mean general COVID-19 knowledge was 22.15 (SD 2.44, range 14–27) indicating a high level of knowledge. The mean pregnancy-specific COVID-19 knowledge 6.84 (SD 2.061, range 0–10) indicated poorer pregnancy-specific knowledge compared with general COVID-19 knowledge. A trend towards higher knowledge was noted with higher income status. Reproductive age women with higher pregnancy-specific knowledge had more positive attitudes toward COVID-19 pregnancy practices.Conclusion Our findings suggest a deficiency in pregnancy-specific COVID-19 knowledge stressing the necessity for targeted public health education interventions. It highlights the need for enhancing COVID-19 pregnancy-specific awareness which can serve as a stepping stone in the success of COVID-19 vaccination campaigns and in halting further disease spread.